Mining tourism and the search for its origins - Rybár, Pavol; Hronček, Pavel (Geotourism/Geoturystyka, 2020)
The article defines concepts related to mining tourism and the reasons why some destinations are chosen as the sites of hundreds of thousands of visitors per year, while others are only visited by “regional fans” of mining history. The authors attempt to ask questions, which will be clarified by formulating a better definition and understanding of mining tourism. Issues discussed include marketing and management of mining tourism, as well as tourists’ preferences. The article focuses on definitions of different forms of tourism, to ultimately argue that mining tourism is a separate type of tourism. A substantial part of the article is devoted to historical personalities, whose activities and interests in historic mining regions of present-day Slovakia can be considered as the beginnings of mining tourism.